When will we have a quantum computer?. (May 2019) - Dyakonov, M.I.
Highlights: A classical computer with N bits at any given moment is in one of its possible 2 N states. In contrast, the state of the hypothetical quantum computer with N qubits is defined by the values of 2 N continuous parameters, the quantum amplitudes. To beat your laptop in performing some special tasks, like factoring very large numbers, one needs ∼1000 qubits. Accordingly, the number of continuous variables that should be under our control is at least 2 1000 ∼ 10 300 . Thus the answer to the question in the title is: as soon as physicists and engineers will learn to control thus number of degrees of freedom, which means NEVER .